MIRAGRODEP with endogenous tariffs 1.0: Documentation - Bouët, Antoine; Laborde Debucquet, David; Traoré, Fousseini (International Food Policy Research Institute, 2022)
MIRAGRODEP with endogenous tariffs is a recursive dynamic multi-region, multi-sector Computable General Equilibrium (CGE) model based on MIRAGRODEP which in turn is based on MIRAGE (Modelling International Relations Under Applied General Equilibrium). It constitutes an extension of the MIRAGRODEP model that allows the user to perform analysis involving endogenous tariffs such as designing optimal common external tariffs (CET) in customs unions. The model is particularly suitable for trade policy analysis that require designing optimal levels of tariffs for regional trade agreements.